Pendekatan Model Nonparametrik untuk Memodelkan Hubungan Antara Jumlah Uang Beredar dan Indeks Harga Konsumen di Indonesia Tahun 1969-2017 - Pardomuan Robinson Sihombing (Indonesian Journal of Applied Statistics, 2020)
Inflation is one of the macroeconomic variables of concern to the government in addition to economic growth, unemployment and poverty. Inflation is measured by the Consumer Price Index (CPI). According to the quantity theory of the classics, argues that the price level is determined by the amount of money in circulation, prices will rise if there is an increase in the money supply, assuming the amount of goods offered is fixed, while the amount of money is doubled, sooner or later the price will doubled. Often the relationship between macroeconomic variables is not always linear, it can be exponential, logarithmic, or highly fluctuating patterns. This nonlinear relationship cannot be forced using parametric regression which generally uses the Ordinary Least Square (OLS) or Maximum Likelihood Estimation (MLE) which often implies the existence of certain distributions and linear data patterns. In some literatures, researches using a linear model with OLS, for describing the relationship between CPI and money supply. This research uses several non parametric approaches, namely kernel and spline functions. The results obtained are a strong positive relationship between money supply and CPI, where money supply has a significantly positive effect on CPI. The most suitable non parametric method to describe the relationship pattern between CPI and money supply is the smoothing spline method with Generalized Cross Validation (GCV) parameter optimization method with the smallest RMSE and MAPE criteria and functions that can follow data patterns smoothly.Keywords: CPI, money supply, non parametric, kernel, spline.